ANALYSIS OF THE APPLICATION OF SCIENCE LITERACYBASED LEARNING BY PUBLIC HIGH SCHOOL TEACHERS IN TARAKAN CITY - Khatimah, Khusnul; Adhani, Aidil; Ilma, Silfia (Biopedagogia, 2024)
Science literacy learning is very important for students to be able to apply science in everyday life. This study aims to analyses the application of science literacy-based learning by state school teachers in Tarakan City. The research method used qualitative with a descriptive approach. The research subjects were seven state high school of Biology teachers with sampling using purposive sampling technique. Dataobtained based on the results of questionnaires and interviews. The results of the research on aspects of scientific knowledge showed that all teachers can distinguish terms in science literacy learning and on aspects of skills, intellectual processes in indicators of generating principles through induction showed all teachers could explain the phenomenon of observation. On the indicator of identifying and controlling variables showed that two teachers experienced problems in identifying and controlling variables and five other teachers could identify and control variables. The indicator of constructing graphs and finding relationships, it showed that all can transform data into tables/graphs, in the indicator of designing and leading investigations, it showed that three teachers did not design themselves, three other teachers design themselves and one other teacher sometimes designs himself and sometimes, they did not design themselves the steps of the practicum, in the indicator of using technology. The results also showed that one teacher did not utilize laboratory equipment and technology and six other teachers utilized equipment and technology in making observations and in the indicator of drawing conclusions from the facts showed that all teachers made conclusions based on facts obtained from observations.